The use of fly ash and metakaolin for the prevention of alkali-silica reaction and delayed ettringite formation in concrete - Silva, A. Santos (2006)
One of the most popular preventive measures to minimize the occurrence of chemical expansive reactions, namely the alkali-silica reaction (ASR) and delayed ettringite formation (DEF) in hardened concrete is the use of supplementary cementing materials (SCMs). Several studies have been performed along the last few years related with the use of fly ashes in the suppression of expansion due to ASR. However, relatively little attention are been focused in its effectiveness to control the DEF in concrete, and the use of metakaolin to control the ASR and DEF. The research work presented in this paper deals with the influence of fly ashes (FA) and metakaolin (MK) in the inhibition of ASR and DEF in concrete. The mechanisms of FA and MK in the suppression of ASR are discussed. Results obtained indicated that the reduction of the calcium hydroxide content is the most beneficial effect of FA and MK in ASR inhibition mechanism. Furthermore, the results obtained indicate that the use of FA and MK, for partial replacement of cement in concrete, is effective in the inhibition of expansion by DEF.